A clinico-statistical study of factors associated with intraoperative bleeding in orthognathic surgery - Keisuke Sugahara; Yu Koyama; Masahide Koyachi; Akira Watanabe; Kiyohiro Kasahara; Masayuki Takano; Akira Katakura (SpringerOpen, 2022)
Abstract Background Excessive bleeding is a major intraoperative risk associated with orthognathic surgery. This study aimed to investigate the factors involved in massive bleeding during orthognathic surgeries so that safe surgeries can be performed. Patients (n=213) diagnosed with jaw deformities and treated with bimaxillary orthognathic surgery (Le Fort I osteotomy and bilateral sagittal split ramus osteotomy) in the Department of Oral and Maxillofacial Surgery at the Suidobashi Hospital, Tokyo Dental College between January 2014 and December 2016 were included. Using the patients' medical and operative records, the number of cases according to sex, age at the time of surgery, body mass index (BMI), circulating blood volume, diagnosis of maxillary deformity, direction of maxillary movement, operative duration, incidence of bad split, injury of nasal mucosa, and blood type were analyzed. Results The results revealed that BMI, circulating blood volume, nasal mucosal injury, and operative time were associated with the risk of intraoperative massive bleeding in orthognathic surgeries. Chi-square tests and binomial logistic regression analyses showed significant differences in BMI, circulating blood volume, direction of maxillary movement, operative duration, and injury to the nasal mucosa. Operative duration emerged as the most important risk factor. Furthermore, a >4-mm upward migration of the posterior nasal spine predicted the risk of massive bleeding in orthognathic surgery. Conclusions The upward movement of the maxilla should be recognized during the preoperative planning stage as a risk factor for intraoperative bleeding, and avoiding damage to the nasal mucosa should be considered a requirement for surgeons to prevent massive bleeding during surgery.